Impact on the profitability and capital adequacy of NRB Commercial Bank before and after COVID 19 pandemic - Khan, Nawaf (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.